Endoscopic necrosectomy is safe in patients with pancreatic walled-off necrosis: Insights from a tertiary center study of 880 procedures - Jensen, Julie Falkebo; Stinne Timmner, Joy; Hadi, Amer; Feldager, Erik; Prahm, August Pilegaard; Ebrahim, Mohamed; Olsen, Gitte Aabye; Roug, Stine; Novovic, Srdan; Karstensen, John Gásdal (Endoscopy International Open, 2025)
Endoscopic transmural drainage with subsequent endoscopic necrosectomy (EN) has become the first-line treatment for acute necrotizing pancreatitis with walled-off necrosis (WON). There is a growing interest in incorporating EN at the index intervention; however, data about the safety of EN are limited. This case series evaluated the rate and type of adverse events (AEs) associated with EN.We retrospectively included consecutive patients with WON from 2012 to 2024 who underwent EN in our tertiary referral center. An AE was defined as any event leading to premature cessation of necrosectomy or requiring intervention either during the procedure or within 24 hours of the procedure.A total of 235 patients and 880 EN procedures (median: 3, interquartile range: 2–5) were recorded. The median age of patients was 57.5 years, of whom 116 were female (49.3%). Snares were used in most procedures (90.9%), EndoRotor in 4.3%, and both were used in 4.8% of procedures. A total of 14 AEs (1.6%) were identified in 11 different patients (4.7%): 13 bleeds and one pneumoperitoneum. In-hospital mortality was significantly higher in the AE group (45.5%) than in the non-AE group (10.3%, P = 0.0004).AEs are rare in EN but are associated with increased mortality.
Keywords: Endoscopic ultrasonography; Intervention EUS; Quality and logistical aspects; Performance and complications